PENINGKATAN POTENSI EKONOMI KREATIF MASYARAKAT MELALUI PEMBUATAN DAN PELATIHAN BUDIDAYA SAYUR KANGKUNG DAN IKAN NILA DENGAN METODE SMART AQUAPONIK - Muskhir, Mukhlidi; Abror, Abror; Irdawati, Irdawati; Luthfi, Afdal; Fajri, Dilham Hidayatul; Ahmad, Nurafni Fajarna Do; Rahman, Muhammad Aulia (Universitas Mataram, 2024)
Siluang Tanjuang Gadang Village faces economic challenges due to limited utilization of agricultural and fisheries resources, including abandoned fish ponds. Internet of Things (IoT) technology with Smart Aquaponics systems offers innovative solutions to increase efficiency and inconvenience. The system combines fish and plant cultivation with real-time monitoring, enabling resource optimization and increased productivity. This service activity aims to increase the efficiency and productivity of IoT-based fish and plant cultivation, as well as increasing community income through modern technology. The program is carried out through four stages: planning, preparation, implementation and evaluation. Activities include installation of the Smart Aquaponics system, community training, and monitoring the use of IoT technology. The results obtained were that the installation of devices on IoT-based Smart Aquaponics tools, such as temperature and humidity sensors, was successful. Training increases the technical capacity of communities, while real-time monitoring helps optimize cultivation conditions. This system increases productivity and operational efficiency, with the potential to increase people's income. The implementation of the IoT-based Smart Aquaponics system in Siluang Tanjuang Gadang Village shows success in optimizing local resources. This technology can increase agricultural and fisheries productivity, as well as encourage economic benefits for village communities.